1998
DOI: 10.1111/j.1469-7793.1998.843bv.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐operation between neural and myogenic mechanisms in the control of distension‐induced peristalsis in the mouse small intestine

Abstract: Myogenic and neural control of intestinal transit were investigated in a model of distension‐induced peristalsis. A comparison was made between the electrical and mechanical activities and outflow of contents observed in control mice and in W/W v mice, which lack the interstitial cells of Cajal associated with Auerbach's plexus. Distension caused a periodic appearance of increased motor activity due to stimulation of enteric nerves in both control and W/W v mice. Excitation was primarily delivered by cholinerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 39 publications
7
89
1
1
Order By: Relevance
“…Others found that the small intestine of the intact W/W v mice and muscle strips in organ bath continue to generate slow waves and RPCs, but both are more irregular in frequency and smaller in amplitude than those in the wild-type mice (Figs. 4, C-F) (45,76,77,80,105). The slow waves and their associated contractions in the W/W v mice propagate over shorter distances than those in the wild-type mice.…”
Section: The Roles Of Icc In the Generation And Propagation Of Slow Wmentioning
confidence: 99%
See 1 more Smart Citation
“…Others found that the small intestine of the intact W/W v mice and muscle strips in organ bath continue to generate slow waves and RPCs, but both are more irregular in frequency and smaller in amplitude than those in the wild-type mice (Figs. 4, C-F) (45,76,77,80,105). The slow waves and their associated contractions in the W/W v mice propagate over shorter distances than those in the wild-type mice.…”
Section: The Roles Of Icc In the Generation And Propagation Of Slow Wmentioning
confidence: 99%
“…The contraction that is solely due to the membrane depolarization by slow wave is called electromechanical coupling. Although these tiny contractions are recordable in in vitro preparations, they do not effectively constrict the lumen in the intact state, and, therefore, they have little or no effect on motility function (77). A good example of these tiny contractions is the quiescent state in the stomach and the small intestine during phase I of the migrating motor complex (MMC) cycle.…”
Section: Pertinent Background On Topics Essential To Evaluate the Rolmentioning
confidence: 99%
“…This was developed further by Bayliss & Starling (1899) with the development of the 'enterograph' which allowed them to record, via a system of levers, movements of the gut wall at several sites simultaneously. Mechanical recordings at several sites along segments of gut have subsequently been made, both in vivo and in vitro, by many workers, allowing some analysis of propagating contractions (Costa & Furness, 1976;Schemann & Ehrlein, 1986;Huizinga et al 1998). An alternative strategy to document gut motility has been to use image analysis of whole segments of gut.…”
Section: Physiological Recordings Of Peristalsismentioning
confidence: 99%
“…For example it will be possible to monitor the activity of significant lengths of intestine while at the same time recording spontaneous or physiologically evoked muscle electrical activity (Gonella, 1971;Tsuchiya, 1972;Yokoyama & North, 1983;Lammers et al 1993). It should also be possible to combine spatio-temporal maps with monitoring of intracellular Ca¥, intracellular recordings from neurons, multiple luminal manometry or strain gauges (Summers & Dusdieker, 1981;Bercik et al 1994;Huizinga et al 1998) and intraluminal flow (Bertuzzi et al 1978;Macagno & Christensen, 1980) to improve the understanding of the biomechanical basis of intestinal motor function. The major limitations of the technique relate to the need for high contrast images with well defined edges, which may limit its use in vivo.…”
Section: Limitations Of Spatio-temporal Mapsmentioning
confidence: 99%
“…Propulsive motility is termed peristalsis and subserved by a complex pattern of neural reflexes that aim to relax intestinal muscle downstream (descending inhibitory reflex) and contract the muscle upstream (ascending excitatory reflex) of the intestinal bolus. Intestinal transit is controlled by both neural and myogenic mechanisms (Huizinga et al, 1998). Several mediators and neurotransmitters govern these motor patterns.…”
Section: Discussionmentioning
confidence: 99%